Surface, structural and mechanical properties of zirconium ablated by KrF excimer laser radiation. (November 2016) - Ali, Nisar; Bashir, Shazia; , Umm-i-Kalsoom; Begum, Narjis; Waqas Ahmad, Syed
Abstract: We study the effect of the ambient – dry (air) and wet (propanol) – environment on the surface, structural and mechanical properties of zirconium samples after irradiation with a KrF excimer laser (wavelength of, pulse duration of and repetition rate of ). The samples are exposed to an increasing number of laser pulses varying from 500 to 2000 in both media. Various features of the treated targets such as surface morphology, chemical composition, crystalline structure and hardness are analysed by complementary characterisation techniques, such as scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), Raman spectroscopy and Vickers hardness tester, respectively. Surface morphology and hardness are explained on the basis of modifications in crystalinity, residual pressures and chemical properties of the sample surface after its irradiation.